Tanjungpura Port as an International Hub Port to Improve Economic Competitiveness: an Overview from International Law - Wiko, Garuda; Kinanti, Fatma Muthia; Syafei, Muhammad; Darajati, Muhammad Rafi; Sudagung, Adityo Darmawan (UI Scholars Hub, 2023)
The Indonesian Government is currently in the process of developing several new ports in its territory as a means of supporting infrastructure development and maritime connectivity. One of them is the Development of the Kijing Terminal Port in the Province of West Kalimantan. It is important to study international and national legal regulations related to ports and how they affect the development of Tanjungpura Port, Kijing Terminal, which will be directed to become one of the international hub ports in Indonesia. The research methodology employed in this study is normative, with in-concreto legal study approach. It is found that, the consequence of the status of the